IMPLEMENTASI KUALITAS LAYANAN DAN PERSEPSI KONSUMEN TENTANG KUALITAS PRODUK TERHADAP KEPUASAN KONSUMEN PADA DEALER WULING TULUNGAGUNG - Moh Irbash Dzikrulloh; Lantip Susilowati (Program Studi Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam IAIN Kediri, 2021)
Service quality in an economic aspect is very important and a challenge for every company. This study aims to determine the extent of the implementation of service quality and consumer perceptions and satisfaction regarding product quality at Wuling Tulungagung Dealer.The method in this study used a qualitative design with data collection methods through interviews and data analysis using content analysis. The findings in this study indicate that the implementation of service quality and consumer perceptions of product quality on customer satisfaction at Dialer Wuling Tulungagung has fulfilled the pillars of success. Its implementation is to provide quality service that has an impact on good consumer perceptions and consumer satisfaction accompanied by quality Dialer Wuling Tulungagung products.